Analisa Manajemen Risiko IT Pada Sistem Informasi Manajemen Proyek Konstruksi dengan ISO 31000 - Dharmawan, Muhammad Rizky; Jazman, Muhammad; Adam, A (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2025)
Information systems are very important for companies to do their daily work. This includes taking care of customer information, handling loans, and keeping track of how well projects are going. But even though information systems are helpful, relying on them more and more can cause problems, especially with data security. PT Sumi Gita Jaya has started using a Corporate Project Management Information System (SIMPP) to make projects run better and to help manage customer information. This research wants to find out the Risk Priority Number (RPN) value to help give advice on how to handle risks in the Company Project Management Information System (SIMPP). The research uses the ISO 31000:2018 method to measure how risky the system is. The steps include finding risks, looking at them closely, calculating the RPN, judging the risks, and deciding what to do about them. This research looks at the level of risk from highest to lowest and provides reviews, treatments, and suggestions for fixing problems caused by risks.